2014
DOI: 10.1007/s10953-014-0219-7
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity Measurements on H2O-Bearing CO2-Rich Fluids

Abstract: Recent studies report rapid corrosion of metals and carbonation of minerals in contact with carbon dioxide containing trace amounts of dissolved water. One explanation for this behavior is that addition of small amounts of H 2 O to CO 2 leads to significant ionization within the fluid, thus promoting reactions at the fluid-solid interface analogous to corrosion associated with aqueous fluids. The extent of ionization in the bulk CO 2 fluid was determined using a flow-through conductivity cell capable of detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(109 reference statements)
0
12
0
Order By: Relevance
“…The increased water activity and clustering 158,159 at elevated temperatures will also likely induce ion formation, which has not yet been detected in wet scCO 2 . 160 Organic ligands and metal−organic complexes, ubiquitous in diverse geologic settings, 147 can be stable at >200 °C and may contribute to reactions in the bulk CO 2 fluid in addition to those in adsorbed nanoscale water films. 26,27 These nonaqueous reactions will lead to carbon cycling among organics, carbonate minerals, and CO 2 fluids.…”
Section: ■ Knowledge Gaps and Research Frontiersmentioning
confidence: 99%
“…The increased water activity and clustering 158,159 at elevated temperatures will also likely induce ion formation, which has not yet been detected in wet scCO 2 . 160 Organic ligands and metal−organic complexes, ubiquitous in diverse geologic settings, 147 can be stable at >200 °C and may contribute to reactions in the bulk CO 2 fluid in addition to those in adsorbed nanoscale water films. 26,27 These nonaqueous reactions will lead to carbon cycling among organics, carbonate minerals, and CO 2 fluids.…”
Section: ■ Knowledge Gaps and Research Frontiersmentioning
confidence: 99%
“…Thermodynamic properties of water/CO 2 mixtures have been extensively measured, mostly at temperatures lower than 373 K, but important discrepancies remain in the phase equilibrium data at higher temperatures . For phase equilibria at elevated temperatures (>473 K) and pressures (>200 bar), which are of particular interest for geochemical applications, there are mainly three sets of experimental measurements from Takenouchi and Kennedy, Todheide and Frank, and Capobianco et al Although these show consistent results for CO 2 solubility in water, the reported equilibrium compositions of the CO 2 -rich phase are in disagreement. A comprehensive review of experimental data for the water/CO 2 mixture is available .…”
Section: Introductionmentioning
confidence: 99%
“…that dissociates to H 3 O + and HCO 3 -. The ion OHis required for dissociation of H 2 CO 3 that is delivered by the autoionization process [26]. The equilibrium reaction (1) is obeying Le Chatelier's principle; the forward reaction is exothermic, an increase in temperature causes reverse reaction.…”
Section: Secondary Factors Methods and Setupmentioning
confidence: 99%
“…The equilibrium reaction (1) is obeying Le Chatelier's principle; the forward reaction is exothermic, an increase in temperature causes reverse reaction. Following [26], the ionic dynamics of…”
Section: Secondary Factors Methods and Setupmentioning
confidence: 99%
See 1 more Smart Citation